2022
DOI: 10.3389/fsurg.2022.985060
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Endoluminal removal of a retrievable conical inferior vena cava filter with a ruptured retraction hook attached to the wall

Abstract: We report the case of a patient who underwent endovascular retrieval of a conical inferior vena cava (IVC) filter with a ruptured retraction hook that was attached to the IVC wall. A 21-year-old woman with a Celect (Cook) filter, implanted 1,522 days prior, requested retrieval. Preoperative ultrasound and CT examinations showed that the filter was inclined, the retraction hook was attached to the IVC wall, and one of the filter’s pedicles was broken. The inferior vena cava was patent, with no thrombus. Old sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been observed that asymptomatic patients, who experienced failed percutaneous removal of filters, showed a lower incidence of complications during midterm follow-up, despite significant penetration of the filter strut [ 28 ].A study reported 21 cases where filters were successfully removed through open surgery after failed endovascular attempts. They either experienced rupture of the filter pillar, abdominal pain, or other reasons, but no postoperative complications occurred after undergoing open surgery [ 29 ]. Therefore, the decision to opt for open surgery for filter removal after unsuccessful intracavitary attempts should be informed by a broader spectrum of real-world cases.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that asymptomatic patients, who experienced failed percutaneous removal of filters, showed a lower incidence of complications during midterm follow-up, despite significant penetration of the filter strut [ 28 ].A study reported 21 cases where filters were successfully removed through open surgery after failed endovascular attempts. They either experienced rupture of the filter pillar, abdominal pain, or other reasons, but no postoperative complications occurred after undergoing open surgery [ 29 ]. Therefore, the decision to opt for open surgery for filter removal after unsuccessful intracavitary attempts should be informed by a broader spectrum of real-world cases.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Difficulty arises in dissecting the filter during surgery if the retrieval hook of the filter has not penetrated the vena cava wall. Moreover, if the posterior wall of the vena cava is penetrated, it will be difficult to separate it under laparoscopic surgery [ 29 ].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The “Loop snare technique”( 29 ) is often used to correct the tilt of a tapered filter and to retrieve the filter when the retrieval hook is attached to the endothelium. However, the “Loop snare technique” is not successful in retrieving the filter when the retrieval hook is adhered to the inner membrane.…”
Section: Discussionmentioning
confidence: 99%
“…ZYLOX filter retrieval kit was introduced but difficulties were encountered when attempting to capture the filter retraction hook. To solve this issue, we utilized a modified loop-snare technique ( 13 ) by introducing a pigtail catheter and a hydrophilic guidewire ( Figure 2E ). The pigtail catheter had its tip partially cut ( Figures 2C,D ) and was rotated to be guided into the interspace between the filter and the SVC wall ( Figure 2B , red arrows).…”
Section: Case Reportmentioning
confidence: 99%